Review on the Application of Graphene/Polymer Composites in Flexible Sensing - Gao Zhengpai (MATEC Web of Conferences)
With the widespread application of flexible electronic devices and neural interfaces, graphene/polymer composites have become a popular research topic in the fields of flexible sensing and biomedical engineering due to their excellent conductivity, mechanical strength, and flexibility. Graphene, as a two-dimensional material, exhibits outstanding properties. However, it faces challenges in practical applications such as poor dispersion, weak interface adhesion, and poor biocompatibility. The introduction of polymer materials can address these issues, improving the flexibility, mechanical properties, and biocompatibility of the composite, thereby enhancing the performance of flexible sensing devices. This paper reviews the progress of graphene/polymer composites in flexible sensing applications. First, the functionalization and dispersion techniques of graphene, as well as the selection and modification methods of polymer materials, are discussed. It is noted that chemical modification and physical dispersion can effectively enhance the stability and interface adhesion of the composites. Second, the paper analyzes strategies for optimizing the performance of composites, including methods for improving mechanical, electrical, and biological properties. Finally, the application examples in flexible sensing are reviewed, highlighting the advantages of these composites in terms of high sensitivity, low power consumption, and long- term stability. Research indicates that graphene/polymer composites have broad prospects in flexible sensing, but issues such as mass production and long-term stability remain to be addressed. Future studies could further explore material interface design and multifunctional development to promote their practical applications in the intersection of electronics and biology.